Environmental DNA Metabarcoding Analysis of Fish Assemblages and Phytoplankton Communities in a Furrowed Seabed Area Caused by Aggregate Mining - Kim, Eun-Bi; Sagong, Hyun; Lee, Ji-Hyun; Kim, Gyungryul; Kwon, Dae-Hyeon; Kim, Yeonghye; Kim, Hyun-Woo (Frontiers in Marine Science, 2022)
To estimate the impact of aggregate mining on a marine ecosystem, fish assemblages and phytoplankton communities were analyzed using environmental DNA metabarcoding. Metabarcoding analysis revealed 152 fish amplicon sequence variants (ASVs) (88 in September and 118 in February), which were assigned to 29 orders, 62 families, 104 genera, and 114 species (73 in September and 89 in February). Heatmap analysis showed that the fish assemblages in the mining area clearly differed from those in the surrounding area and that Pagrus major, Lateolabrax japonicus, Zeus faber, and Eopsetta grigorjewi were significantly more abundant there than in the surrounding area. In the phytoplankton community in September, the phyla Cyanobacteria and Haptophyta differed significantly between the mining area and its surroundings. By contrast, no such significant differences were identified in February, presumably due to the low temperature impeding phytoplankton growth. Taking these findings together, mining activities clearly affect fish and phytoplankton communities, but further long-term study is required to assess their impacts on marine ecosystems.